Multiwalled Carbon Nanotube Filters for Toxin Removal from Cigarette Smoke - Pandey, Sumit Kumar; Vishwakarma, Pramod Kumar; Yadav, Sunil Kumar; Shukla, Prashant; Srivastava, Anchal (American Chemical Society, 2019)
The fatal diseases and disorders caused by smoking have raised a serious concern for worldwide public health. So for its prevention, it has become very necessary to develop various types of filter material for the removal of carcinogenic and other toxic elements present in cigarette smoke. Herein, we demonstrate a novel filter for cigarettes, fabricated by the insertion of multiwalled carbon nanotubes (MWCNTs) based thin flexible membrane into the conventional cellulose acetate filter. The developed filter has attractive attributes of high filtering efficiency, lightweight, flexible, cost-effective, and scalable production. This flexible MWCNTs membrane has been fabricated using a simple vacuum-assisted filtration technique followed by the synthesis of MWCNTs using a cost-effective spray pyrolysis technique. The filter shows excellent performance for the removal of PM2.5, having a removal efficiency of ∼99%. It also shows a significant ability to remove nicotine, tar, and toxic heavy metals such as lead present in cigarette smoke.
Keywords: Heavy metals; MWCNTs membrane; Nicotine; Particulate matter; Tar